TATHWÎR MAWÂD AL-MUTHÂLA’AH AL-MUTADARIJAH LI AL-TA’ALLUM AL-DZÂTÎ LI AL-THULLÂB AL-MUTAKHARIJÎN FI MADÂRIS ‘ÂMMAH - Ridha Darmawaty; Ahmad Saidi; Inna Muthmainnah; Mardhiya Agustina (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
The research employed a research and development method modified from Borg and Gall, consisting of needs assessment, design, and development. The research objectives were to portray the material of teaching Arabic written in class ten at Islamic senior high school and design a model of enrichment material graded and used independently for the students who graduated from public junior high schools. The study showed that the students who graduated from public junior high school and continued study to Islamic senior high school must be assisted by an enrichment material for their independent study because the existing material did not match their previous knowledge. In this research, a model of teaching material was designed based on three characteristics; first, readability is the main character of supporting teaching material. Secondly, grammar and daily culture made it easier to grab meaning and were thirdly graded and comprehensive. The teaching material was accompanied by audio material for listening, conversation, and reading to the substitute teacher when the student studied independently.